PRINSIP DASAR WASATHIYAH DALAM PANDANGAN AL-QUR’AN - Yani, Ahmad (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2022)
The theme of wasathiyah (moderation) of Islam is a very important and interesting theme to be reviewed. Many parties, both individuals and institutions, have reviewed the theme both on a national and international scale. Academics, intellectuals and thinkers who are concerned with contemporary Islamic discourse are certain to follow the dynamics of the discourse. Likewise, Islamic da'wah institutions, special wabils who often represent Islamic institutions in government. A positive perspective positions various reviews related to Islamic wasathiyah (moderation) in various media as a sign of the scientific spirit and Islamic passion among Muslims. However, it is necessary to strengthen and deepen the perspective and foundation of Islamic wasathiyah, so that later it can be socialized and become a correct and adequate reference, seeing that some of the perspectives that have been socialized about wasathiyah are even out of the essence and substance of wasathiyah itself. Among the strengthening and deepening of the wasathiyah theme is looking for the basic principles and meaning of wasathiah from the Qur'an. The basic principles of wasathiyah in the perspective of the Qur'an are important to review, because the signs and contents of the Qur'an are full of inspiration that can continue to develop and can be used as a guide in the dynamics of Islamic thought specifically regarding wasathiyah (moderation). This study uses a qualitative method with a literature review. The conclusion of this study is, the basic principles of Islamic wasathiyah in the view of the Qur'an are: the principle of justice (al'adl), the principle of convenience (at-taisir), the principle of goodness, privilege (al-khairiyah), the principle of wisdom ( al-hikmah), the principle of consistency (istiqamah) and the principle of balance (tawazun).